Childbearing desires of childless men and women: When are goals adjusted? - Reimondos, A; Gray, E; Evans, A (My University, 2013)
This paper examines the concept of desired future fertility. Childbearing desires are often conceptualized in the literature as representing an individual's ideal future fertility where there are no constraints or obstacles to achieve the desired outcome. As such, childbearing desires, unlike fertility intentions, are thought to be relatively unaffected by changing life circumstances. Using a theoretically driven model incorporating goal adjustment, we test whether desires of childless men and women do in fact change over time. Using data from the Household, Income and Labour Dynamics in Australia (HILDA) survey (2001–2010) we specifically investigate whether changing life circumstances do effect a change in childbearing desires. We find that age is strongly related to adjusting childbearing desires, as is relationship formation. Desires are however, not greatly influenced by short-term shocks such as an episode of poor health or unemployment, although these events have different effects for women and for men. Overall, the findings are consistent with psychological theories of goal adjustment, that is, individuals will revise their desires for having children if they perceive that their desires are not likely to be fulfilled.
Keywords: Families -- Fertility; Life Events; Families and relationships; Disadvantage, adversity and resilience; Families; Life Events; Fertility; Dsiadvantage, adversity and resilience; Families and relationships; Adversity and resilience